Occupational burnout phenomenon among the employees of the Agricultural Social Insurance Fund involved in collection of unduly drawn benefits - Brzękowska, Magdalena (Ubezpieczenia w Rolnictwie – Materiały i Studia, 2023)
This paper presents a set of externalities and internalities which determine the behaviour and quality of tasks performed by public officers in the context of early occupational burnout syndrome following the experience of the author and of the employees of the Agricultural Social Insurance Fund (KRUS). Investigated is the impact of said factors on the level of adverse stress among employees dealing with selected issues associated with the recovery of monies under unduly drawn pension and disability benefits, sickness and care allowances, as well as other benefits for farmers and their family members, and consequently, impacting early occupational burnout in this occupational group of office staff. This paper draws from the literature, the outcome of an interview with KRUS employees, as well as from their long-standing experience and selected methods of coping with stress at work. The paper aims to set forth solutions to prevent early occupational burnout among public officers.